2000
DOI: 10.1088/0022-3727/33/5/308
|View full text |Cite
|
Sign up to set email alerts
|

Model of the cathode region and gas temperature of a dc glow discharge at high current density

Abstract: A model is reported of the cathode region of a dc glow discharge at high current density. The distributions of most important plasma species (such as fast electrons, fast neutrals and ions, and energetic sputtered metal atoms) are determined either analytically or using simple semi-analytic methods, taking into account possible strong gas-density/temperature gradients. A heat-transfer equation is used to calculate the gas temperature, and the power-deposition profiles due to fast neutrals and energetic metal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(156 reference statements)
0
8
0
Order By: Relevance
“…'Fluid' models have been developed both for low and high pressure discharges. Arslanbekov [17] developed a model to simulate the cathode region and gas temperature of a low pressure direct current glow discharge. Recently Yuan et al [18] reported the development of a fluid model to study atmospheric pressure radio frequency glow-discharges in helium.…”
Section: Introductionmentioning
confidence: 99%
“…'Fluid' models have been developed both for low and high pressure discharges. Arslanbekov [17] developed a model to simulate the cathode region and gas temperature of a low pressure direct current glow discharge. Recently Yuan et al [18] reported the development of a fluid model to study atmospheric pressure radio frequency glow-discharges in helium.…”
Section: Introductionmentioning
confidence: 99%
“…This is also due to the bombardment of the cathode surface by ions launched from the plasma and accelerated in the strong electric field in the cathode fall and by fast neutral molecules created in collisions with ions in the cathode fall. The cathode temperature has a significant influence on the properties of the cathode fall [26][27][28][29][30][31] and on the cathode vaporization rate. In addition, the vaporization rate and the gas temperature determine the saturation state of the vapour in the gas which in turn determines the concentration and size of the primary particles.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive self-consistent modeling of cathode sputtered helium-copper laser discharges with different hollow-cathode configurations was carried out by Arslanbekov, Tobin, and Kudryavtsev. 22,23 In these models the discharge volume is divided into the negative glow, which is assumed to be ''field free,'' and the cathode sheath, where the voltage drop occurs. In all cases a set of coupled rate equations is solved for the densities of ionic and neutral species in the negative glow.…”
Section: B Modeling Of Hollow-cathode Laser Dischargesmentioning
confidence: 99%
“…The wall temperature is assumed to be 350 K, the temperature jump occurring at the walls is treated in the same way as given in Ref. 23. The complete temperature distribution is utilized in the fast electron, sputtered metal thermalization and ''negative glow'' parts of the model, temperature averaged over the sheath at a given radius is used in the ''cathode sheath'' block.…”
Section: E Gas Temperaturementioning
confidence: 99%